The Man Who Created the Middle East : A Story of Empire, Conflict and the Sykes-Picot Agreement - Sykes, Christopher Simon, 1948- (London William Collins, 2016)
The story of the catastrophic British mishandling of the Middle East, told through the career of Sir Mark Sykes - Edwardian aristocrat, traveller, writer, politician and co-author of the infamous 1916 Sykes-Picot agreement, a shady deal between Entente powers to carve up the Middle East that lies at the heart of many of region's problems today. At the age of only 36 Sir Mark Sykes was signatory to a reviled and notorious treaty, drawn up in May 1916 between the French and the British, that divided up the collapsing Ottoman Empire in the event of an allied victory in World War One. Written without any Arab involvement, it negated an earlier promise that the British Government had made to the Arabs that they would gain independence. Drawn up in secret, a controversy has raged around it ever since
Include Illustration, Notes and Index
Keywords: Sykes, Mark, 1879-1919 -- Middle East -- Great Britain